Forkhead transcription factor FOXO1 is involved in hypoxia/reoxygenation-induced gonadotropin-releasing hormone decline. Issue 18 (16th December 2020) - Shi, Chun; Li, Guihua; Guo, Han; Liu, Xintong
Abstract : Previously, it has been demonstrated that aging is associated with nuclear factor-κB (NF-κB)-mediated hypothalamic gonadotropin-releasing hormone (GnRH) decrease. The hypothalamus is one of the brain regions that are vulnerable to ischemia-reperfusion injury. However, it is unclear whether ischemia-reperfusion has an influence on the hypothalamic GnRH release. In the current study, GT1-7 cells, which are a cell line of hypothalamic GnRH neurons, were subjected to hypoxia-reoxygenation to mimic ischemia-reperfusion. The effect of hypoxia-reoxygenation on the hypothalamic GnRH release was investigated. It was found that GnRH secretion from GT1-7 cells was decreased under the hypoxia-reoxygenation condition. Mechanistic studies revealed that hypoxia-reoxygenation activated nuclear factor-κB (NF-κB) via the protein kinase B (Akt)/forkhead box protein O1 (FOXO1) pathway, thereby inhibiting gnrh1 gene. The results of the current study suggested that hypoxia-reoxygenation injury may facilitate the hypothalamic programming of system aging through impairment of hypothalamic GnRH release.